COMMUNITY BANK AS THE PHILOSOPHICAL RATIO LEGIS BEHIND THE PROHIBITION OF ISLAMIC RURAL BANKS FROM OFFERING DIRECT DEBIT IN CONSTITUTIONAL COURT RULINGS: Impacts and Solutions in The Digital Financial Era - Kadir, Abdul; Musataklima, Musataklima (Fakultas Syariah, 2024)
The unequal legal treatment between Commercial Banks (CB) and Rural Banks (BPR) in providing direct debit services has prompted some parties to file a judicial review of the Banking Law with the Constitutional Court (MK). Through Decision Number 32/PUU-XX/2023, the MK rejected the petition, reasoning that BPR/BPRS are community banks. This study aims to uncover the ratio legis of the community bank concept, the impact of prohibiting direct debit services on Islamic Community Banks amidst the development of Islamic fintech and the National Non-Cash Movement (GNNT), and the collaboration between Islamic Community Banks and Islamic fintech as a sustainability strategy. This is doctrinal legal research using case and statutory approaches, relying on primary and secondary legal materials obtained through library research and analyzed prescriptively. The study reveals that the prohibition of direct debit services for Islamic community banks is based on concerns about undermining their philosophical function to serve economically disadvantaged groups. The limitations and restrictions on payment transaction services have hindered the optimal performance of Islamic community banks in serving the public, particularly micro and small enterprises, thereby affecting sustainable national economic growth. Nevertheless, Islamic community banks can sustain their operations in the digital finance era by collaborating with Islamic fintech lending platforms to enhance their service offerings. Perbedaan perlakuan hukum antara Bank Umum (BU) dan Bank Perkreditan Rakyat (BPR) dalam penyediaan layanan direct debit mendorong sejumlah pihak untuk mengajukan uji materi terhadap Undang-Undang Perbankan ke Mahkamah Konstitusi (MK). Melalui Putusan Nomor 32/PUU-XX/2023, MK menolak permohonan tersebut dengan alasan bahwa BPR/BPRS adalah bank komunitas. Penelitian ini bertujuan untuk mengungkap ratio legis dari konsep bank komunitas, dampak pelarangan layanan direct debit pada Bank Perkreditan Rakyat Syariah (BPRS) di tengah perkembangan fintech syariah dan Gerakan Nasional Non-Tunai (GNNT), serta kolaborasi antara BPRS dengan fintech syariah sebagai strategi keberlanjutan. Penelitian ini merupakan penelitian hukum doktrinal dengan pendekatan kasus dan perundang-undangan, menggunakan bahan hukum primer dan sekunder yang diperoleh melalui studi pustaka dan dianalisis secara preskriptif. Hasil penelitian menunjukkan bahwa pelarangan layanan direct debit bagi BPRS didasarkan pada kekhawatiran akan melemahkan fungsi filosofis mereka untuk melayani kelompok ekonomi lemah. Pembatasan dan larangan pada layanan transaksi pembayaran telah menghambat kinerja optimal BPRS dalam melayani masyarakat, khususnya usaha mikro dan kecil, sehingga memengaruhi pertumbuhan ekonomi nasional yang berkelanjutan. Meski demikian, BPRS dapat mempertahankan operasinya di era keuangan digital dengan berkolaborasi bersama platform pinjaman fintech syariah untuk meningkatkan kualitas layanan mereka.